Trace Element Biogeochemistry in the High‐Latitude North Atlantic Ocean: Seasonal Variations and Volcanic Inputs - Achterberg, Eric P.; Steigenberger, Sebastian; Klar, Jessica K.; Browning, Thomas J.; Marsay, Chris M.; Painter, Stuart C.; Vieira, Lúcia H.; Baker, Alex R.; Hamilton, Douglas S.; Tanhua, Toste; Moore, C. Mark; Steigenberger, Sebastian; 1 Ocean and Earth Science, National Oceanography Centre Southampton University of Southampton Southampton UK; et al. (Global Biogeochemical Cycles, 2021)
We present dissolved and total dissolvable trace elements for spring and summer cruises in 2010 in the high‐latitude North Atlantic. Surface and full depth data are provided for Al, Cd, Co, Cu, Mn, Ni, Pb, and Zn in the Iceland and Irminger Basins, and consequences of biological uptake and inputs by the spring Eyjafjallajökull volcanic eruption are assessed. Ash from Eyjafjallajökull resulted in pronounced increases in Al, Mn, and Zn in surface waters in close proximity to Iceland during the eruption, while 3 months later during the summer cruise levels had returned to more typical values for the region. The apparent seasonal removal ratios of surface trace elements were consistent with biological export. Assessment of supply of trace elements to the surface mixed layer for the region, excluding volcanic inputs, indicated that deep winter mixing was the dominant source, with diffusive mixing being a minor source (between 13.5% [dissolved Cd, DCd] and −2.43% [DZn] of deep winter flux), and atmospheric inputs being an important source only for DAl and DZn (DAl up to 42% and DZn up to 4.2% of deep winter + diffusive fluxes) and typically less than 1% for the other elements. Elemental supply ratios to the surface mixed layer through convection were comparable to apparent removal ratios we calculated between spring and summer. Given that deep mixing dominated nutrient and trace element supply to surface waters, predicted increases in water column stratification in this region may reduce supply, with potential consequences for primary production and the biological carbon pump. Key Points: Bio‐essential element concentrations in surface waters decreased from spring to summer with removal ratios reflecting biological uptake. Effects of volcanic inputs from Eyjafjallajökull in spring 2010 were pronounced for Al, Mn, and Zn but returned to typical levels in summer. Deep winter convection dominated trace element supply to surface waters with minor contributions from atmospheric and diffusive mixing. GEOMAR Helmholtz ...